Exploring the Impact of Sustainability Development Education to Environmental Literacy of BPE Students - M. A. Pevida; F. P. Rivera; M. L. Amacna; M. R. Potenciando (American Journal of Physical Education and Health Science, 2026)
This descriptive-correlational study aims to ascertained the level of sustainability development education and environmental literacy among BPE students and scrutinized the relationship between these variables. Environmental knowledge is crucial to providing sufficient awareness to address these ecological issues that are currently expanding throughout this generation. Due to the rise of environmental problems, it is imperative for future PE teachers to examined their ways of handling eco-friendly practices. Quantitative research was implemented, using a modified survey instrument to gather data collection from a sample of 328 BPE students at the University of Mindanao – Main Campus. The mean and standard deviation, two samples of descriptive statistics, were utilized to assess the degrees of sustainability development education and environmental literacy. Additionally, the Spearman rho correlational investigation was conducted to identify the important connection between these variables. The results revealed that the level of sustainability development education and the level of environmental literacy are very high level. However, the findings found a weak relationship between sustainability development education and environmental literacy, revealing factual data that demonstrated a subtle correlation between these factors. The findings show that there is an integral need to incorporate environmental themes and educational interventions to change the attitude and behaviors regarding sustainability. The results have significance for improving curriculum design, environmental programs, and meaningful discussions, highlighting the importance of integrating sustainable practices and ecological awareness.